Detection of Volatile Organic Compound with an Ion Mobility Spectrometry Cell Type Device with a Corona Discharge Ionization Source - Boggio, Norberto Gabriel; Pierpauli, Karina Alejandra; Rinaldi, Carlos Alberto; Lamagna, Alberto (American Scientific Publishers, 2011)
Fil: Boggio, Norberto Gabriel. Comisión Nacional de Energía Atómica. Gerencia del Área de Investigación y Aplicaciones No Nucleares. Gerencia Física (Centro Atómico Constituyentes). Proyecto Tandar; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina